Newfoundlanders Remember Their Past - Olga Spence - Memorial University of Newfoundland. Extension Service
Newfoundlanders Remember Their Past is a 5 part television series that was created by Extension Service, Memorial University of Newfoundland for Memorial University Television to highlight some of the films and interviews done in the past through Extension Services. In episode 2 of this series host Charles Callanan looks at the film series "The Port au Choix Project," filmed in 1969, specifically the film "The Past, The Present, The Future" which highlights an interview with Olga Spence who shares her experiences as a mother, a widow, her struggles with the government and her opinion of services in her community. As part of the introduction to the film Charles Callanan interviews Paul McCleod.